Recycling of marble waste: A review based on strength of concrete containing marble waste - Tunc, Esra Tugrul (Academic Press Ltd- Elsevier Science Ltd, 2019)
It is necessary to prioritize recycling applications to contribute to the marble industry, ecology, and economy. In the current study, it is seen that the waste marble is used extensively in concrete instead of aggregate and cement. Thus, the aim involved minimizing the harmful effects of waste marble on the environment. Furthermore, the effects of waste marble on the strength of concrete were investigated. Recycling options for waste marble were explored in detail based on a review of previous studies. The results indicated that the use of waste marble in concrete in certain rates was adequate to replace the coarse/fine aggregate, cement, and admixture material and that the resulting concrete exhibited higher strength. Additionally, in the current study, practical equations were developed to calculate the compressive strength and splitting tensile strength in concrete that contains waste marble. A fairly good fit was obtained between the calculated and measured values for both compressive strength and splitting tensile strength. The scientific value of the study was illustrated via a demonstration that indicated that the use of waste marble in concrete production was beneficial and provided useful equations to determine the compressive strength and splitting tensile strength of concrete without experimentation.
Keywords: Recycling; Waste marble; Aggregate; Concrete; Strength